Design and Construction of a Water Quality Monitoring System Using GSM. - Murangi Ezra (Kabale University, 2023)
Along with the increasing use of water in our communities, the quality of water needs to be considered, more especially water for human and animal consumption. Usually, the quality of water is determined based on the value of the turbidity of water. Therefore, this project develops a global system for mobile communication water quality monitoring system using its turbidity. Specifically, the values of the water turbidity in the water under investigation are utilized. The turbidity sensor consists of a photodiode and an infrared light emitting diode. Measurements of water turbidity is based on the principles of light scattering in the water. A turbidity sensor is used to detect the intensity of light passing through the scattering of particles and the result is an analog signal voltage. The signal of the turbidity sensor entering the micro-controller i.e., Arduino will be processed. The measurement result is Nephelometric Turbidity Unit (NTU) but converted into a percentage. Then are displayed on the liquid crystal display screen. The turbidity measurement range on the system are between 0-NTU to 40-NTUs but expressed into a percentage. The developed system can monitor the water turbidity automatically and a message is sent on to the mobile phone hence help in checking the quality of water.